Hepatic blood flow in late sepsis patients - Amany Abd El Maqsoud; Abir Zakaria; Fayrouz Shoukry (SpringerOpen, 2013)
Background Systemic inflammatory response syndrome (SIRS), sepsis, and severe sepsis influence total hepatic blood flow. However there are conflicting data on the time of its assessment, methodology, study design, and differentiation in terms of whether the condition is an experimental SIRS, sepsis, or a human clinical syndrome. Objective of the studyThe aim of this study was to assess the total hepatic blood flow and the contribution of hepatic arterial blood flow (HABF) and portal venous blood flow using a Doppler vascular ultrasound in SIRS, sepsis, and severe sepsis patients, aiming at a clear prognostic parameter that can predict the patient's outcome. Results There was a clear cutoff point of 16.09 ml/min for HABF, above which the hazard ratio for death was 5.6046, with a 95% confidence interval of 2.0078-15.6451 and a P-value of 0.0011 in late sepsis patients. The predictive potential for this HABF cutoff for patient mortality showed a sensitivity of 80%, specificity of 73.7%, positive predictive value of 70.6%, negative predictive value of 82.4%, 95% confidence interval of 0.612-0.907, and P-value of less than 0.0004. There was a significant positive correlation between the HABF and APACHE II scores (P=0.023). Cox regression analysis showed that only the APACHE II score and HABF were independent predictors for patients' outcome. Conclusion Duplex ultrasound assessment was a useful bedside method for predicting mortality in late sepsis patients through estimation of HABF, with a reasonable predictive potential at a definite cutoff level.